Toxicological Effect Of Entomopathogenic Fungus Beauveria Bassiana (Balsamo) Vuillemin. Against Malaria Vector Anopheles Stephensi (L.) - A. PRASAD; B.VEERWAL (International Journal of Pharma and Bio Sciences, 2012)
Diseases transmitted by mosquitoes have become one of the important issues regarding public health. Malaria still kills million of people in developing countries like Africa and Asia. However, development of resistance towards insecticides has made the standard approach for vector control unsustainable and researches have turned towards finding environmentally safe ways to kill the vectors of malaria. To achieve this goal biological control agents such as Entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin are being considered as a favourable eco-safe agent for vector control of malaria. In the present investigation, different developmental stages of Anopheline mosquitoes were treated with four different concentrations i.e.1.5, 2.0, 2.5 and 3.5 ml of 6.4×1011 conidia/ ml of Beauveria bassiana (Balsamo) Vuillemin. Percent mortality at different stages revealed positive co-relation with concentration, although 2nd instar was highly susceptible stage.LC50 for 2nd instar was minimum 0.907 percent followed by 1.265, 1.196 and 2.727 for 1st, 3rd and 4th instars respectively. Various morphological abnormalities and fungal sporulations were observed in majority of treated stages whereas control stages had no sporulations. Hence, the fungal bio pesticide Beauveria bassiana(Balsamo)Vuilemin could be a potential bio control agent for mosquito control.